Periodontal Management of Sturge-Weber Syndrome - Butchibabu Kalakonda; Koppolu Pradeep; Ashank Mishra; Krishnanjaneya Reddy; Tupili Muralikrishna; Vijaya Lakshmi; Radhika Challa (Case Reports in Dentistry)
Sturge-Weber syndrome (SWS) is a sporadic disorder and is frequent among the neurocutaneous syndromes specifically with vascular predominance. This syndrome consists of constellation of clinical features like facial nevus, seizures, hemiparesis, intracranial calcifications, and mental retardation. It is characterized by focal port-wine stain, ocular abnormalities (glaucoma), and choroidal hemangioma and leptomeningeal angioma most often involving occipital and parietal lobes. The present paper reports three cases of SWS with oral manifestations and periodontal management, which included thorough scaling and root planing followed by gingivectomy with scalpel and laser in cases 1 and 3 consecutively to treat the gingival enlargement. However, the treatment in case 2 was deferred as the patient was not a candidate for periodontal surgery.